Study of the formation of gas-vapor in the liquid mixture - Pavlenko, Anatoliy; Koshlak, Hanna; Cheilytko, Andrii; Nosov, Maksym (Eastern-European Journal of Enterprise Technologies, 2016)
Equilibrium conditions of the pore former agent in the material during the formation of the porous structure, pressure and temperature of the pore former agent gas inside the closed spherical pore, heat transfer between the growing pore and the surrounding mixture were researched. The calculation of the gas vapor area was made with obtained equations. This calculation needs for prediction of pore growth dynamics. Obtained dependences show that, in general, the peak values of the growth speed of vapor volume, movement of the pore boundary, mass flow, heat flow have smaller values under lower periods of oscillations. The character of changing of the calculation quantities under 130 oC and 180 oC are the same. This temperature range was chosen, because real swelling happens under the same range. Obtained equation of the overheat temperature of the pore former agent gas inside the pore clarifies the temperature (180 oC), under which the inertial period of formation of the gas microphase in the first heating stage is missing. The equilibrium conditions give a chance to assess energy parameters of the swelling process under stabilization of the predictable pore sizes. During the calculation of the pressure inside the closed spherical pore it was found that the bigger the difference between the chemical potentials of material-pore systems, the lower the gas pressure inside the pore. Since the convective heat transfer in a gas is directly proportional to the pressure, next statement can be made: to achieve minimum heat transfer of pore, it’s necessary to increase the difference between the chemical potentials of material-pore systems. Obtained methodology allows finding conditions of controlled swelling and conditions of controlled structure formation of the material with predicted thermophysical properties. It can be real only, because this methodology takes into account physical properties of the raw mixture, the chemical potential of the mixture components, levels of energy influence on the raw mixture and the impact of all above factors on the size of the gas-vapor area (pore). The differences of new methodology allow predicting the porosity of thermal insulating material and its thermophysical properties. These results are proposed to use in designing technological processes of production of porous materials for various purposes.